2022
DOI: 10.1002/ar.24870
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial growth and morphology among intersecting clinical categories

Abstract: Differential patterns of craniofacial growth are important sources of variation that can result in skeletal malocclusion. Understanding the timing of growth milestones and morphological change associated with adult skeletal malocclusions is critical for developing individualized orthodontic growth modification strategies. To identify patterns in the timing and geometry of growth, we used Bayesian modeling of cephalometrics and geometric morphometric analyses with a dense, longitudinal sample consisting of 15,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
2
1
0
Order By: Relevance
“…Second, specialized growth patterns of each skeletal types could be noticed. For crania and maxilla morphology, our results indicated relatively smaller value of Ptm-A, smaller SNA and NA-FH in hypodivergent group, echoing previous studies which suggested that maxilla of this group was generally shorter and posteriorly positioned than the hypodivergent facial type [ 19 , 20 ]. Sagittally, maxilla of Class II tends to be longer and more protrusive than Class III [ 19 , 20 ], as larger value of Ptm-A and NA-FH in Class II group could also be revealed by our study in Table 3 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Second, specialized growth patterns of each skeletal types could be noticed. For crania and maxilla morphology, our results indicated relatively smaller value of Ptm-A, smaller SNA and NA-FH in hypodivergent group, echoing previous studies which suggested that maxilla of this group was generally shorter and posteriorly positioned than the hypodivergent facial type [ 19 , 20 ]. Sagittally, maxilla of Class II tends to be longer and more protrusive than Class III [ 19 , 20 ], as larger value of Ptm-A and NA-FH in Class II group could also be revealed by our study in Table 3 .…”
Section: Resultssupporting
confidence: 86%
“…For crania and maxilla morphology, our results indicated relatively smaller value of Ptm-A, smaller SNA and NA-FH in hypodivergent group, echoing previous studies which suggested that maxilla of this group was generally shorter and posteriorly positioned than the hypodivergent facial type [ 19 , 20 ]. Sagittally, maxilla of Class II tends to be longer and more protrusive than Class III [ 19 , 20 ], as larger value of Ptm-A and NA-FH in Class II group could also be revealed by our study in Table 3 . From the aspect of mandible morphology, shorter and retrognathic positioning of mandible was also found in hyperdivergent group represented by shorter Go-Po and Go-Co, smaller FH-NPo and SNB.…”
Section: Resultssupporting
confidence: 86%
“…There was no statistically significant change in ANS-PNS/SN results, and we can assume that the palatal plane position remained relatively stable after treatment with Herbst appliances. After a period of follow-up, there was a statistically significant change in the results of MP/SN, ANS-PNS/MP, and we can conclude that after treatment with Herbst appliances, the position of the lower jaw plane remained relatively unstable, and the angle with the skull base plane and the palatal plane showed a trend of decreasing, according to the research results of a large number of scholars, for patients with class II class 1 classification, most of them belonged to the vertical growth type (Schulz, Koos et al, 2016;Knigge, Hardin et al, 2022), and the lower jaw had a tendency to grow in the direction of the open type. From this, we can infer that the functional appliance has a certain blocking and guiding effect on the patient's growth type during the treatment process, and after the treatment is over, the intervention is removed, and there is a certain tendency of rotation in the mandibular plane to the direction of the closed mouth type, that is, the opposite trend of the original growth type.…”
Section: Analysis Of Outcome Measuresmentioning
confidence: 73%